Effective Use of Twitter by Orthopaedic Sports Medicine Journals Can Result in Increased Impact Factor - Katina Kartalias, M.D., M.S; Tessa R. Lavorgna, B.S; Shreya M. Saraf, M.S; Mary K. Mulcahey, M.D; Christopher J. Tucker, M.D (Elsevier, 2024)
Purpose: To determine whether activity on Twitter was correlated with increasing impact factor (IF) among 6 orthopaedic sports medicine journals. Methods: Twitonomy software was used to collect account activity for the American Journal of Sports Medicine; Arthroscopy: The Journal of Arthroscopic and Related Surgery; Knee Surgery, Sports Traumatology, Arthroscopy; Journal of Shoulder and Elbow Surgery; Orthopaedic Journal of Sports Medicine; and Sports Health. Data from 2000 to 2020 were collected. Each journal's annual IF score was collected via scijournal.org. A multivariate regression model was used to predict the influence of different Twitter metrics on IF from 2012 to 2019. The journal name, number of tweets, and interaction of the two were used to predict IF. Additionally, Pearson correlation was used to assess correlations between Twitter account metrics and IF. Results: Over the study period, all IFs increased, with the exception of that for American Journal of Sports Medicine. The effect size between number of tweets and IF was not the same for each journal. For every additional tweet, American Journal of Sports Medicine increased its IF by 0.001 (P = .18). Sports Health and Orthopaedic Journal of Sports Medicine increased their IF by 0.01 (P = .002) and 0.022 (P < .001), respectively. Knee Surgery, Sports Traumatology, Arthroscopy would expect a decrease in its IF by 0.004 (P = .55) and Journal of Shoulder and Elbow Surgery and Arthroscopy would increase its IF by 0.002 (P = .71) and 0.001 (P = .99), but this was not significant. There was a statistically significant positive correlation between annual tweets and IF across all journals. Conclusions: Markers of Twitter account activity, specifically the number of annual tweets, were predictive of an increase in IF among the orthopedic sports medicine journals included in this study. Clinical Relevance: The findings of this study may allow orthopaedic sports medicine journals to make more effective, targeted, and productive use of their social media accounts to reach a broader audience, increase their influence, and increase the IF of their journal.